The Effect of Coronary Angiography Timing on Cardiac Surgery Associated Acute Kidney Injury Incidence and Prognosis - Liu, Kang; Li, Meiyuan; Li, Li; Wu, Buyun; Xu, Xueqiang; Ge, Yifei; Mao, Huijuan; Xing, Changying (Frontiers in Medicine, 2021)
Introduction: Acute kidney injury has been identified as a common complication of cardiac surgery. To date, the effect of the time interval from coronary angiography to cardiac surgery on postoperative acute kidney injury is still controversial. The aim of this study was to investigate the relationship between the timing of coronary angiography and cardiac surgery associated acute kidney injury. Methods: 813 patients who underwent coronary angiography and cardiac surgery successively from January 2017 to December 2018 were included in this retrospective cohort study. We applied multivariate logistic regression, propensity score analysis and subgroup analysis to evaluate the association between the time interval and postoperative acute kidney injury incidence and prognosis. Meta-analysis was conducted to verify the results. Results: The overall incidence of the cardiac surgery associated acute kidney injury was 28.8%. Age (OR=1.046, 95%CI: 1.017-1.075), cardiopulmonary bypass (OR=3.439, 95%CI: 1.316-8.986) and diabetes (OR=2.522, 95%CI: 1.439-4.417) were found to be independent risk factors of postoperative acute kidney injury in multivariate logistic regression and propensity score analysis. Undergoing cardiac surgery within 7 days after coronary angiography was not associated with increased incidence of postoperative acute kidney injury or worse prognosis. Meta-analysis obtained consistent results. Conclusions: The time interval shorter than 7 days had no influence on cardiac surgery associated acute kidney injury incidence and prognosis. The decision of delaying the surgery should be made after comprehensive evaluation of the patient.